Estabilidad cromática de resina compuesta sometida a los sistemas de pulido y pigmentos comerciales y naturales–2025 - Celis Carrillo, Caroline Celeste (2025)
The present study aims to establish the difference in the color stability of composite resin subjected to different polishing systems and commercial and natural pigments in the year 2025. The research is quantitative in nature, with a quasi-experimental design. The study was conducted using the entire population, consisting of 84 resin discs measuring 2 mm in thickness and 8 mm in diameter, made of photopolymerizable resin A1 (Z350 XT, 3M). These were divided into groups of 28 discs, and each group was polished using a different system (rubber polishers, Sof-Lex discs, and Astrobrush). Four discs from each group were immersed in six different pigments (coffee, wine, Coca Cola, annatto, turmeric, and chicha) and distilled water, resulting in 12 discs immersed in each solution. Data were collected at 7 and 14 days. The 84 resin discs were equally distributed among the three polishing systems, with 28 discs assigned to each system, representing 33.3% per group (rubber polishers, Sof-Lex discs, and Astrobrush). Similarly, the 84 discs were equally divided and immersed in six pigments and distilled water, with 12 discs in each group (coffee, wine, Coca-Cola, annatto, turmeric, chicha, and distilled water), representing 14.3% of the total. After 7 days, a total of 20 out of the 84 resin discs showed color stability, with 12 samples belonging to the control group and 8 samples immersed in Coca-Cola and polished with rubber polishers and discs; only the samples polished with Astrobrush and immersed in distilled water maintained their color stability. The greatest number of samples showing color variation corresponded to shade A2, with a total of 28 discs, predominantly those immersed in wine and coffee, with 8 discs each, belonging to the group polished with rubber polishers and discs. The polishing system does not provide color stability against commercial and natural pigments; however, samples polished with rubber polishers and Sof-Lex discs showed less color variation compared to those polished with Astrobrush.